The specific features of T cell immunity in breast cancer - L. V. Skotarenko; I. K. Vorotnikov; Z. G. Kadagidze; F. A. Shamilov (ABV-press, 2014)
The fact that the formation and growth of malignancies occur with pronounced immune impairments is beyond question now. In the past de- cades, great progress has been made in the studies of the immunology and immunotherapy of malignancies, including breast cancer. Despite intensive studies of the specific features of cell immunity in breast cancer, many points remain to be inadequately studied sofar and the avail- able information is controversial and scarce, which calls for further studies.